A rare case of Levofloxacin induced ventricular arrhythmia: Levofloxacin induced ventricular arrhythmia (GAIMS Journal of Medical Sciences, 2023)
Drug induced cardiac arrhythmias are seen commonly in clinical practice. Amongst drugs, antibiotics have a specific predisposition, and amongst them, macrolides and fluoroquinolones are specifically seen to have such a tendency. However, amongst fluoroquinolones, the rate of incidence of quinolone induced cardiac arrhythmia is reported as 5.4 cases per 10 million prescriptions. Here, we report a rare case of a probable Adverse Drug Reaction (ADR) i.e., Left Ventricular inferoposterior surface bigeminy recorded 24 hours after initiation of levofloxacin which disappeared after 24 hours of its discontinuation.